Effects of Hospital Clowning on Anxiety and Fatigue in Children with Cancer undergoing Chemotherapy - Asma Nikkhah-Beydokhti; Fereshteh Ghaljaei; Narjes khatoun Sadeghi; Fereshteh Najafi (Mashhad University of Medical Sciences, 2021)
Background: Chemotherapy is associated with various physical and psychological complications such as fatigue and anxiety in children. Although hospital clowning completely affects health care in pediatric patients, it is a little-known distraction approach in children undergoing chemotherapy in Iran. Aim: This study aimed to investigate the effect of hospital clowning on anxiety and fatigue in children with cancer undergoing chemotherapy. Method: The participants in this clinical trial were 7-15-year-old children (n = 18) with cancer undergoing chemotherapy in a hospital in southeastern Iran, 2019. Participants were selected using convenience sampling and randomly assigned to the intervention (n=40) and control groups (n=40). The intervention group and clown participated in different games for two weeks, 3 sessions per week, and each session lasted 2 to 3 hours in the playroom of the oncology ward. The control group received routine care. A demographic survey, the Revised Children's Manifest Anxiety Scale (RCMAS), and the Visual Analog Fatigue Scale (VAFS) were completed before and immediately after the intervention by interviewing the two groups. Data were analyzed by IBM SPSS v.21 using the Independent t-test, Paired t-test, and Chi-square. Results: The mean and standard deviation of the age in the intervention and control groups were 9.61±2.84 and 9.65±2.28 years old, respectively. The mean difference between anxiety and fatigue in the two groups was significantly different after hospital clowning (p <0.001). Implications for Practice: The present study indicated that hospital clowning reduced anxiety and fatigue in children with cancer undergoing chemotherapy. Using hospital clowning is recommended in clinical wards due to the negative effects of anxiety and fatigue on the treatment of children with cancer.